2021
DOI: 10.29303/jppipa.v7ispecialissue.962
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Problem Base Learning Model combined with E-STEM Based Student Worksheets on Learning Outcomes and Self Efficacy on Environmental Pollution Materials

Abstract: The learning process has not emphasized the development of skills; this is because in learning students tend to memorize concepts so that learning outcomes and self-efficacy are not trained optimally. The formulation of the problem in this study is: is there a difference in learning outcomes and student self-efficacy between the use of the Problem Base Learning model combined with the E-STEM-based Student Worksheet with the Problem Base Learning model on environmental pollution material at MAN Banda Aceh? This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…13 articles reported STEM intervention in the form of classroom-based learning, workshop, internship, and field study activities using the STEM approach, all reporting a positive impact on knowledge and skills. This finding aligns with global academic research, which indicates that participation in STEM learning benefits learners, including improved learning outcomes and attitudes towards learning, creativity, and the acquisition of 21st-century skills (Amalya et al, 2021;Celiker, 2020;Chen & Chen, 2021;Oschepkov et al, 2022;Sheffield et al, 2017;Yildirim, 2016). Academics agree that STEM education could provide a rich learning experience by giving opportunities to learn and address more related and relevant real-world problems by integrating the disciplines (Bybee, 2013;English, 2016;Glancy & Moore, 2013;Vasquez et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…13 articles reported STEM intervention in the form of classroom-based learning, workshop, internship, and field study activities using the STEM approach, all reporting a positive impact on knowledge and skills. This finding aligns with global academic research, which indicates that participation in STEM learning benefits learners, including improved learning outcomes and attitudes towards learning, creativity, and the acquisition of 21st-century skills (Amalya et al, 2021;Celiker, 2020;Chen & Chen, 2021;Oschepkov et al, 2022;Sheffield et al, 2017;Yildirim, 2016). Academics agree that STEM education could provide a rich learning experience by giving opportunities to learn and address more related and relevant real-world problems by integrating the disciplines (Bybee, 2013;English, 2016;Glancy & Moore, 2013;Vasquez et al, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…Research has shown that STEM learning is advantageous to students, e.g. a positive impact on learning outcomes (Amalya et al, 2021;Yildirim, 2016), cultivating learning attitude, technical thinking, and creativity (Chen & Chen, 2021;Oschepkov et al, 2022) and contribute to developing 21st-century skills (Celiker, 2020;Sheffield et al, 2017). Undeniably, the teacher who facilitates the learning experience for students drives success in STEM learning.…”
Section: Teacher and Pre-service Teacher On Stem Educationmentioning
confidence: 99%
“…Poor quality education results in the potential benefits of education not being realized. It is in line with the fact that Aceh Province has poor quality education, ranking 27th out of 34 provinces in Indonesia in 2019 (Amalya et al, 2021). The low quality of education in Aceh Province results from the inadequate educational facilities and infrastructure that are owned and accompanied by the low quality of teachers at all levels of education (Abd Majid, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…In this study, teacher candidates' perceptions, attitudes, and behavioral orientations were improved after joining the design-based STEM activities about renewable energy sources. In the literature, students' perception, knowledge, and attitude variables towards the environment were increased with problem-based E-STEM activities (Amalya et al, 2021). As a result of this, the sense of responsibility and awareness of students improved, and their environmentally friendly behaviors improved thanks to E-STEM applications.…”
Section: Discussionmentioning
confidence: 99%